2018
DOI: 10.1007/s00214-018-2345-6
|View full text |Cite
|
Sign up to set email alerts
|

The molecular electrostatic potential analysis of solutes and water clusters: a straightforward tool to predict the geometry of the most stable micro-hydrated complexes of β-propiolactone and formamide

Abstract: High-resolution microwave spectroscopic studies have recently revealed the structures of six microhydrated complexes of β-propiolactone (BPL) as well as five microhydrated complexes of formamide. Complexes containing one to three water molecules were selected as model systems to set a methodological approach based on the study on the isolated partner for the identification of the most stable microhydrated complexes. A four-step study revealed to be particularly straightforward for the identification and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…41 The most stable isomer for the TMAO:(H 2 O) 3 isomer was already identified in the literature: it is composed of three water molecules solely interacting with the TMAO. Such a structure significantly differ to "water segregation" [30][31][32][33][34][35][36][37] The most stable isomer for the TMAO:(H 2 O) 5 complex can be considered as the beginning of encapsulation (Figure 8): if we assimilate, as a first approximation, the TMAO molecule to a sphere centered on the nitrogen atom, about a fourth of this sphere is covered by an incomplete water layer. It is interesting to further notice that the beginnings of this encapsulation follow a spheroid arrangement of water molecules, with a diameter close to 9 Å in the equatorial axis ( Figure 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The most stable isomer for the TMAO:(H 2 O) 3 isomer was already identified in the literature: it is composed of three water molecules solely interacting with the TMAO. Such a structure significantly differ to "water segregation" [30][31][32][33][34][35][36][37] The most stable isomer for the TMAO:(H 2 O) 5 complex can be considered as the beginning of encapsulation (Figure 8): if we assimilate, as a first approximation, the TMAO molecule to a sphere centered on the nitrogen atom, about a fourth of this sphere is covered by an incomplete water layer. It is interesting to further notice that the beginnings of this encapsulation follow a spheroid arrangement of water molecules, with a diameter close to 9 Å in the equatorial axis ( Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is interesting to note that TMAO does not lead to segregation of water molecules, unlike other solutes. [30][31][32][33][34][35][36][37] The fact that the most stable TMAO:(H 2 O) 2 and TMAO:(H 2 O) 3 isomers consist of isolated water molecules interacting with the solute rather than slightly perturbed water dimer and water trimer can easily be understood by considering the interaction energies between the TMAO and a single water molecule on the one hand, and between water molecules in the water dimer and water trimer on the other hand. Indeed, the interaction energy between a single water molecule and TMAO is equal to -61.4 kJ.mol -1 (Table 2) Nona2: D0 = -67.9 kJ.mol…”
Section: Identification and Characterization Of Tmao:(h 2 O) 2-9 Isomersmentioning
confidence: 99%
“…It was previously suggested that a quantitative comparison of electrophilic and nucleophilic sites on a solute with those available on water clusters seems to provide interesting clues regarding how water/solute interactions can occur: the presence of a more electrophilic or nucleophilic site on the solute compared to water clusters could lead to their dissociation; otherwise, a segregation of water molecules seems more favorable. 21 Thus, the electrophilic and nucleophilic sites available on the H 2 CO, Cl 2 CO, F 2 CO, (NC) 2 CO and H 2 CCO solutes on the one hand and on the water clusters on the other hand, were quantitatively characterized. None of the selected solute contains a more nucleophilic site than the highest nucleophilicity on oxygen atom of the water molecules (Figure 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Gadre and Pundlik , have developed a predictive model based on the topological analysis of V ( r ): in the electrostatic potential for intermolecular complexation (EPIC) model, , the structure of a noncovalent complex is investigated through the characterization of the most electrophilic site of one partner and the most nucleophilic site of another partner. The EPIC model avoids the complex geometry optimization step, since the optimal geometry and the interaction energy are estimated from isolated partners , It appears, however, that in the case of complexes involving simultaneous interactions between several electrophilic and nucleophilic sites of the partners, this approach does not enable the identification of all the isomers that may be formed. , It is worth noting in passing that Gadre’s team has also developed other approaches for larger systems, such as the cluster-building algorithm as well as the molecular tailoring approach (MTA). , …”
Section: Introductionmentioning
confidence: 99%
“…The number of solvents that minimizes Δ G solv is then taken for further investigations. Alternative approaches are based on an analysis of the molecular electrostatic potential to identify interaction sites [ 21 , 22 , 23 ]. Following a related idea, Sure et al proposed a protocol based on the analysis of the screening charge densities [ 24 ].…”
Section: Introductionmentioning
confidence: 99%